Odpowiedź:
5.
u = -1
w = 2
a)
3u + w - 5 = -3 + 2 - 5 = -6
b)
7 - uw = 7 + 2 = 9
c)
u + 1/4w = -1 + 2 * 1/4 = -1 + 1/2 = -1/2
d)
(5 - u)/w = (5 + 1)/2 = 6/2 = 3
e)
w(3 - u) = 2(3 + 1) = 2 * 4 = 8
f)
(3w + u) : 2 = (3*2 - 1) : 2 = 5/2 = 2 1/2
6.
a)
x = -2
y = 3
(x + 5)(y - 2) = (-2 + 5)(3 - 2) = 3 * 1 = 3
b)
a = 4
b = 2
(2a - 3)(5 - 3b) = (2*4 - 3)(5 - 3*2) = (8 - 3)(5 - 6) = 5 * (-1) = -5
c)
s = -2
t = 2
(3s + t)(5t - 8) = (-3*2 + 2)(5*2 - 8) = (-6 + 2)(10 - 8) = -4 * 2 = -8
d)
u = -1
w = 5
(5u - w)(2w + 3u) = (-5 - 5)(2*5 - 3) = -10 * (10 - 3) = -10 * 7 = -70
Szczegółowe wyjaśnienie: